HUBUNGAN KECERDASAN INTRAPERSONAL DENGAN GAYA BELAJAR VISUAL, AUDITORI, DAN KINESTETIK (VAK) - Nurhasmiranti; Alia Fatimah; Devi Viona Fitria; Raja Muhammad Syarwandi; M. Jaya Adiputra (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Learning is influenced by two factors, namely internal factors and external factors. Internally one of the influencing factors is the learning style or way of learning. Differences in learning styles in students must really be observed by the teacher so that children can develop the intelligence they have well. There are eight types of child intelligence, one of which is intrapersonal intelligence. Intrapersonal intelligence is an ability to understand feelings within oneself. In this article, researchers will analyze whether there is a significant relationship between intrapersonal intelligence and visual, auditory, and kinesthetic learning styles (VAK). The method used is quantitative with correlation analysis. The technique used is Pearson Product Moment with the instrument used is a questionnaire. The results of the study show that there is a relationship between intrapersonal intelligence and visual, auditory, and kinesthetic learning styles (VAK). There is a significant relationship between intrapersonal intelligence and visual learning style with a fairly strong level of relationship and a correlation coefficient value of 0.509. Likewise, the auditory learning style has a low level of relationship with a correlation coefficient value of 0.339. And the kinesthetic learning style has a fairly strong relationship with a correlation coefficient value of 0.505.